Residual effect of phosphorus sources on the presence and absence of organic compost in the production of beet and chicory in subsequent cultivation of broccoli - Cardoso, Antonio I. I. [UNESP]; Silva, Priscilla N. L. [UNESP]; Fernandes, Dirceu M. [UNESP]; Lanna, Natália B. L. [UNESP]; Colombari, Lidiane F. [UNESP]; Nakada-Freitas, Pâmela G. [UNESP] (FapUNIFESP (SciELO), 2024)
The utilization of organic fertilizer for a short cycle crop may allow planting, in sequence, another short cycle crop, without the need for new fertilizers, reducing the costs of a new fertilization. The objective of this study was to evaluate the residual effect of fertilization applied to broccoli with phosphorus sources in the presence and absence of organic compost, on beet and chicory production in subsequent cultivation. In broccoli cultivation, four sources of phosphorus (thermophosphate, natural phosphate, natural reactive phosphate, and triple superphosphate) (600 kg/ha of P2O5) were evaluated in the presence and absence of organic compost (Visafértil®, 55 t/ha) before planting. After the removal of the cultural remains of broccoli, beet and chicory, seedlings were transplanted in the same plots of the first crop treatments. For each species eight treatments were evaluated, in a 4 x 2 factorial scheme. The first factor were the four sources of phosphorus and the second one was the application or not of organic compost before broccoli (hybrid BRO 68) planting. Treatments with organic compost showed greater production of beet and chicory, compared to the absence of compost. Fertilization with organic compost associated to the phosphorus sources provides necessary residual effect to beet and chicory production. The best P source for beet was triple superphosphate, and for chicory, in the absence of organic compost, triple superphosphate was the best source. In the presence of organic compost, the best sources were triple superphosphate and natural phosphate.
Efeito residual de fontes de fósforo na presença e ausência de composto orgânico na produção de beterraba e chicória em cultivo sucessivo de brócolis
Keywords: Beta vulgaris; Cichorium endivia L; phosphate fertilization; residual organic fertilizer; successive cultivation